The Strategy for Higher Education Development: European Requirements, Metrics, Problems - Georgiev, Rumen; Velushev, Milen (Research Papers, 2019)
At present, the topic of necessary change in the higher education system of Bulgaria is becoming more frequent in public discussions. This is why today, less than two years before the end term of the strategy for development of the higher education in Bulgaria in the period 2014- 2020, it is high time to review its content, application and effect in order to establish whether it is successful and use this analysis to outline possible improvements for the next one. Our study is based on the premise that the strategy should create conditions for overcoming the contradictions accompanying the division of labor in the society and the lifelong development of the competences of labor resources as follows from the quadruple helix model of innovation. The methodology of the analysis is based on the principle of economic efficiency and the suggested indicators, measures and effects of each of them are examined from the point of view of public benefits and public costs. We reached conclusions regarding which formulations and measures included in the resent strategy for the development of higher education are not serving the public interest and should be replaced with others, subjected to a qualitatively new philosophy regarding the role of higher education.